2021
DOI: 10.1002/jemt.23712
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex‐multiphoton microscopy and computational strategy for biomedical imaging

Abstract: We demonstrate the benefit of a novel laser strategy in multiphoton microscopy (MPM). The cheap, simple, and turn‐key supercontinuum laser system with its spectral shaping module, constitutes an ideal approach for the one‐shot microscopic imaging of many fluorophores without modification of the excitation parameters: central wavelength, spectral bandwidth, and average power. The polyvalence of the resulting multiplex‐multiphoton microscopy (M‐MPM) device is illustrated by images of many biomedical models from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Moreover, various optical studies described in the literature present the two-photon excitation and emission spectra of fluorescence of NADH and FAD and three-photon excitation of tryptophan or nucleic acids. [23][24][25][26][27][28] All of these studies display a twophoton excitation range of NADH and FAD located between 700 and 850 nmas we have measuredand an emission range, centered at 450 nm covering the range between 400 and 600 nm. This spectral range corresponds to the emission range we have detected.…”
Section: Origin Of the Endogenous Emission Of Fluorescence From Bacteriamentioning
confidence: 61%
See 2 more Smart Citations
“…Moreover, various optical studies described in the literature present the two-photon excitation and emission spectra of fluorescence of NADH and FAD and three-photon excitation of tryptophan or nucleic acids. [23][24][25][26][27][28] All of these studies display a twophoton excitation range of NADH and FAD located between 700 and 850 nmas we have measuredand an emission range, centered at 450 nm covering the range between 400 and 600 nm. This spectral range corresponds to the emission range we have detected.…”
Section: Origin Of the Endogenous Emission Of Fluorescence From Bacteriamentioning
confidence: 61%
“…The emitted signal could originate from a part or a totality of these substances such as protein tryptophan, a few other aromatic amino acids, nucleic acids, and some coenzymes. [21][22][23] The emission spectra resulting from these substances emitting an endogenous signal of fluorescence cover most of these spectral ranges. [21] According to these authors, the influence of flavin adenine dinucleotide (FAD) and nicotinamide-adenine dinucleotide (NAD) are considered to be major.…”
Section: Origin Of the Endogenous Emission Of Fluorescence From Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the resolution in the optical plan (perpendicular to the optical axis) of about 250 nm at best and the resolution in the optical axis is about 1.5 µm at best. But we have recently demonstrated that in a biological sample constituted by many scattering or absorbing elements, or in case of specific laser excitation properties, this optimal of resolution decreases quickly [9], towards 0.4 µm in the optical plane and 2.3 µm in the optical axis.…”
Section: Introductionmentioning
confidence: 99%
“…Label-free imaging modalities of TPEF and ThPEF become possible thanks to the autofluorescence from various endogenous chromophores such as NAD(P)H, flavin adenine dinucleotide, collagen, elastin, tryptophan, etc These substances in living biological structures can have 2-photon/3-photon absorption in a wide wavelength range and emit broadband autofluorescence. 19 Consequently, 2 different substances may have a large portion of spectral overlap for both absorption and emission, and thus careful attention should be paid to select the proper combination of the excitation and detection wavelength in order for a convincing differentiation.…”
Section: Introductionmentioning
confidence: 99%